The Altering Eye Contemporary International Cinema - Phillip Kolker, Robert (Open Book Publishers, 2009)
The Altering Eye covers a "golden age" of international cinema from the end of WWII through to the New German Cinema of the 1970s. Combining historical, political, and textual analysis, Kolker develops a pattern of cinematic invention and experimentation from neorealism through the modernist interventions of Jean-Luc Godard and Rainer Maria Fassbinder, focusing along the way on such major figures as Luis Buñuel, Joseph Losey, the Brazilian director Glauber Rocha, and the work of major Cuban filmmakers. Kolker's book has become a much quoted classic in the field of film studies providing essential reading for anybody interested in understanding the history of European and international cinema. This new and revised edition includes a substantive new Preface by the author and an updated Bibliography.